AKTIVISME DIGITAL & RUANG PUBLIK: ANALISIS PERCAKAPAN KOMUNIKASI PADA TAGAR #RESETINDONESIA DI PLATFORM X - Fathiya Nisrina Athari; Nuriyatul Lailiyah (Interaksi Online, 2026)
The development of digital technology has transformed patterns of political participation in society through the practice of digital activism on social media. The #ResetIndonesia hashtag on platform X emerged during the August 2025 political demonstrations as a symbol of digital resistance against government policies. The objective of this study is to identify the themes of public conversations formed within the digital activism of #ResetIndonesia and to examine the forms of emotions expressed in these conversations. This research employs a qualitative approach with a descriptive research type using Braun dan Clarke’s thematic analysis method. The data were collected from tweets containing the #ResetIndonesia hashtag on platform X during the period of August 28 to September 11, 2025 through a web scraping technique. Findings reveal five dominant themes: sentiment toward government institutions, the crisis of justice in Indonesia, reflections on national conditions, acts of resistance, and public solidarity. The discourse manifests intense affective engagement through emotions such as anger, hatred, and hope. Grounded in theories of digital activism, connective action, and affective publics, this research explains how personal emotions in digital spaces can form networks of collective political participation on social media.